Use of Mohr diagrams to predict fracturing in rock masses, with applications for predicting sub-surface behavior - D.C.P. Peacock; David J. Sanderson; Bernd Leiss (iScience, 2024)
Summary: Mohr diagrams are a simple and effective method that can help geoscientists consider, model, and predict the ranges of mechanical properties of rock, stresses, fluid pressures, and the resultant fractures that are likely to occur in the sub-surface. Mohr diagrams can be used to make predictions about how rocks may respond to change, with a transition from a stable state to fracturing occurring if there are changes in (1) the failure envelope, (2) stresses, and/or (3) fluid pressure.This article uses Mohr diagrams to address two questions of significance to the energy transition. First, how will metasedimentary rocks, which are potential geothermal reservoir rocks, respond to thermal stimulation? Second, will fractures that may influence the underground storage of radioactive waste develop in a clay sequence during exhumation? Mohr diagrams are shown to be useful for highlighting misconceptions and input data problems, leading to improved understanding of how structures develop.